2012
DOI: 10.3758/s13415-012-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

Vocal emotions influence verbal memory: Neural correlates and interindividual differences

Abstract: Past research has identified an event-related potential (ERP) marker for vocal emotional encoding and has highlighted vocal-processing differences between male and female listeners. We further investigated this ERP vocal-encoding effect in order to determine whether it predicts voice-related changes in listeners' memory for verbal interaction content. Additionally, we explored whether sex differences in vocal processing would affect such changes. To these ends, we presented participants with a series of neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 67 publications
15
81
0
Order By: Relevance
“…Emotion-specific modulation of the Late Positive Component (LPC) has been observed for speech prosody (Paulmann et al, 2013;Schirmer et al, 2013), with a more positive-going wave at central-posterior brain sites for expressions high in arousal Paulmann et al, 2013;Jessen & Kotz, (2011) who reported no significant LPC amplitude differences for anger, fear, and neutral vocalizations in the "audio" condition of their study). Here, the LPC amplitude between 450-700ms was strongly influenced by both voice and emotion type;…”
Section: Late Decoding Stages: Cognitive Elaboration Of Social Signifmentioning
confidence: 88%
See 3 more Smart Citations
“…Emotion-specific modulation of the Late Positive Component (LPC) has been observed for speech prosody (Paulmann et al, 2013;Schirmer et al, 2013), with a more positive-going wave at central-posterior brain sites for expressions high in arousal Paulmann et al, 2013;Jessen & Kotz, (2011) who reported no significant LPC amplitude differences for anger, fear, and neutral vocalizations in the "audio" condition of their study). Here, the LPC amplitude between 450-700ms was strongly influenced by both voice and emotion type;…”
Section: Late Decoding Stages: Cognitive Elaboration Of Social Signifmentioning
confidence: 88%
“…These later cognitive stages have been tied to alterations in N300 (Bostanov & Kotchoubey, 2004) or N400 (Liu, Rigoulot, & Pell, 2015;Paulmann & Pell, 2010;Schirmer & Kotz, 2003) responses to non-linguistic and speech-embedded emotions, respectively, using priming or conflict paradigms that pair emotional voices with a related or unrelated stimulus (word or face). Recent data have also linked ongoing semantic analysis of vocal emotion expressions to changes in the Late Positive Component (LPC), which exhibits differences according to emotion type (Jessen & Kotz, 2011;Paulmann et al, 2013;Schirmer et al, 2013). For example, it was reported that LPC amplitudes differ significantly for six basic emotions, and a stronger positivity was generally observed for expressions high in arousal, at central-posterior brain regions approximately 400-800ms post-onset of emotional prosody (Paulmann et al, 2013).…”
Section: Erp Studies Of Vocal Emotion Expressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diferentiation of P200 amplitude can be found between basic emotions [6] or between emotional vs. neutral speech [3,7], suggesting that this component may relect an early function of "tagging" emotional or motivational relevant stimuli. The P200 tended to be associated with higher mean and range of f0, larger mean and range of amplitude of speech, and slower speech rate [6], implicating that the early P200 modulation is partially explained by early meaning encoding as well as continued sensory processing [8]. A late centro-parietal positivity (also named LPC) evoked by vocal emotion expressions has been deined as a positive-going wave starting about 500 ms post-onset of the vocal stimuli and perhaps sustaining until 1200 ms depending on stimulus features.…”
Section: Introductionmentioning
confidence: 99%